Surface modification of calcium carbonate nanoparticles as hydraulic oil additives friction performance research - Yuan-sheng Ding; Hou Baoquan; Xv Zhai; Fei Lu (Functional Materials, 2018)
In this experiment, calcium carbonate nanopartilces were prepared by metathesis method. The calcium carbonate powders were modified by sodium dodecyl sulfonate. The characteristics of raw and modified calcium carbonate powders were analyzed and characterized by various methods. The size of the unmodified nano-calcium carbonate is about 2.7 μm, and the particle size of the modified particles is about several hundred nanometers. The CFT-1 material performance tester was utilized to evaluate the tribological characteristics of the additive. The data show that the modified nano-calcium carbonate can improve the anti-friction and anti-friction performance of hydraulic oil.